A comparison of endoscopic and non-endoscopic biliary intervention outcomes in patients with prior bariatric surgery - Kamboj, Amrit K.; Pidlaoan, Victorio; Shakhatreh, Mohammad H.; Hinton, Alice; Conwell, Darwin L.; Krishna, Somashekar G. (Endoscopy International Open, 2018)
Background and study aims Endoscopic biliary intervention (BI) is often difficult to perform in patients with prior bariatric surgery (BRS). We sought to analyze outcomes of patients with prior BRS undergoing endoscopic and non-endoscopic BI. Patients and methods The Nationwide Inpatient Sample (2007 – 2011) was reviewed to identify all adult inpatients (≥ 18 years) with a history of BRS undergoing BI. The clinical outcomes of interest were in-patient mortality, length of stay (LOS), and total hospital charges. Results There were 7,343 patients with prior BRS who underwent BIs where a majority were endoscopic (4,482 vs. 2,861, P < 0.01). The mean age was 50±30.8 years and the majority were females (80.5 %). Gallstone-related disease was the most common indication for BI and managed more often with primary endoscopic management (2,146 vs. 1,132, P < 0.01). Inpatient mortality was not significantly different between patients undergoing primary endoscopic versus non-endoscopic BI (0.2 % vs. 0.7 %, P = 0.2). Patients with sepsis were significantly more likely to incur failed primary endoscopic BI (OR 2.74, 95 % CI 1.15, 6.53) and were more likely to be managed with non-endoscopic BI (OR 2.13, 95 % CI 1.3, 3.5). Primary non-endoscopic BI and failed endoscopic BI were both associated with longer LOS (by 1.77 days, P < 0.01 and by 2.17 days, P < 0.01, respectively) and higher hospitals charges (by $11,400, P < 0.01 and by $ 14,200, P < 0.01, respectively).Conclusion Primary endoscopic management may be a safe and cost-effective approach for patients with prior BRS who need BI. While primary endoscopic biliary intervention is more common, primary non-endoscopic intervention may be used more often for sepsis.